Peningkatan Kualitas Pembelajaran di Sekolah Dasar melalui Inovasi Media Interaktif: Studi Pengabdian di SDN 2 Ngindeng - Sasongko, Yogi Banar; Nasif, Hifni; Farhah, Farhah; Naufal Dafa, Abdul Karim; Marshandi Abi Nur Y, Achmad Ghovva (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
Strengthening the quality of learning at the elementary school level requires adaptive and innovative strategies, especially in the digital era, which demands a more engaging and participatory learning process. This community service activity was carried out at SDN 2 Ngindeng in response to the need to increase teacher capacity in designing and using interactive learning media appropriate to the local context. The main objectives of this activity were: (1) to improve teachers' skills in using interactive media, (2) to increase active student engagement in the learning process, and (3) to foster a culture of simple technology-based learning. The community service methods used included teacher training, mentoring in the implementation of interactive media in the classroom, as well as pre- and post-test-based evaluations of teachers and observations of student engagement. The community service results showed a significant improvement in teacher skills, with an average post-test score of 26 points. Furthermore, student engagement increased from 55% to 82% after the program was implemented. These findings demonstrate that interactive media-based learning innovations can be a strategic solution for improving the quality of elementary education, particularly in areas with limited resources.